CFD Simulation of a 100 MWth Lithium Combustion Slag Tap Furnace as a basis for an Energy Storage Process. (May 2017) - Maas, P.; Schiemann, M.; Scherer, V.; Fischer, P.; Taroata, D.; Schmid, G.
Abstract: Lithium combustion has been discussed as a possible basis for a closed energy loop. While the reaction products in conventional combustion processes are gaseous, the reaction products of lithium combustion are solid (Li2 CO3, Li2 O) and hence easy to capture and to recycle. The current paper describes the lay-out and optimization of a 100 MWth lithium slag tap furnace by computational fluid dynamics (CFD) using CO2 as oxidizer for the lithium. ANSYS Fluent has been extended by a lithium combustion model developed by the authors. Simulations with five different gas and particle injection angles and three atmospheres with different CO2 -fuel ratios were conducted to investigate the lithium conversion level and separation efficiency. The simulations show, that a high separation efficiency of lithium combustion products is possible when a large injection angle is used. The conversion level on the other hand is highly dependent on both injection angle and CO2 -fuel ratio and lies between 84 and 87.6%.